Prenatal Ultrasound Diagnosis of Unilateral Pulmonary Agenesis - Eduardo Reyna-Villasmil; Liliana Briceño-Sanabria; Juan Carlos Briceño-Sanabria; Carlos Briceño-Pérez (Journal of Medical Ultrasound)
Pulmonary agenesis (PA) is a rare developmental malformation, with a frequency of approximately 1 in 10–15,000 pregnancies. Unilateral PA is often associated with other congenital anomalies, whereas bilateral PA is fatal. Prenatal diagnosis is rare and is diagnosed more frequently in the postnatal period than in the prenatal period. Is a challenge that may be difficult as it shares similar features with other more common pathologies. Ultrasound plays a crucial role in early diagnosis and management. Ultrasonographic findings for a correct prenatal diagnosis include mediastinum displacement with the absence of parenchymal or cystic tissue, decreased thoracic volume, an elevated diaphragm, cardiac axis deviation, and a hemithoracic cavity largely occupied by the heart. Cases of right PA have a worse prognosis compared to left PA, probably due to higher frequency of cardiac and great vessel abnormalities. A rare case of early prenatal ultrasound diagnosis of unilateral fetal PA, at 18 weeks of gestation, is reported.